Simplified computer incident response model for premium pension limited Nigeria - Abubakar Mohammed, 1989- author; Norafida Ithnin; Fakulti Komputeran (2014)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia,2014